A structural analysis of the EFQM model: an assessment of the mediating role of process management - Suárez, Eva; Roldán, José L.; Calvo-Mora, Arturo (Journal of Business Economics and Management, 2014)
The purpose of this paper is to research how the critical total quality management (TQM) factors present in the European Foundation for Quality Management (EFQM) model make up a management system. This article presents a significant contribution to the current body of TQM by establishing the model’s internal working structure as a management system and also by showing how the way in which the organization designs and starts up this system has a bearing on its results. The methodology used is structural equation modeling (Partial Least Squares technique). The sample consisted of 116 firms. Our findings show that: (1) the EFQM model is a reliable and valid framework to measure the results achieved by the firm; (2) The synergies between the critical factors make up a management system, especially, the importance of leadership, strategy and processes for the system’s effectiveness and soundness; (3) The obtaining of a measure of the overall results. This allows us to have an overall indicator of the level of excellence attained by the firm; (4) The process management fully mediates the influence of strategy, and alliances and resources management respectively on overall results.